Food texture and viscosity : concept and measurement - Bourne, Malcolm C. (Food science and technology (Academic Press), 1982)
Drawing together literature from a myriad of sources, this book focuses on the texture and viscosity of food as well as the techniques for measuring these properties. Food Texture and Viscosity: Concept and Measurement includes a brief history of the field and its basic principles and then goes on to provide a detailed discussion of the physical interactions between the human body and food, objective methods of texture measurements, commercially available instruments and their uses, various types of viscous flow, and sensory methods for measuring texture and viscosity. An appendix lists names and addresses of suppliers for anyone interested in purchasing equipment. Incorporating material from numerous sources across a wide range of disciplines, this book will prove valuable to students, faculty, researchers, and anyone working in food technology and sensory evaluation.